Optimalisasi Manajemen Tenaga Pendidik dan Kependidikan dalam Meningkatkan Mutu Pendidikan di Era Digital - Yusrianti, Itel; Susanti, Eri (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the optimisation of teaching and education personnel management in improving the quality of education in the digital era. The approach used is qualitative with a literature study method through analysis of various sources related to technology-based education management strategies, administrative automation, and the development of educators' digital competencies. The results of the study show that the use of digital technology in education management can increase work efficiency, strengthen collaboration, and support a more adaptive learning process through the use of Learning Management Systems (LMS), digitisation of administrative services, and continuous training programmes for teachers and educational personnel. However, its implementation still faces challenges in the form of infrastructure limitations, variations in digital literacy levels, and resistance to change. Therefore, optimising management requires an integrated strategy through strengthening infrastructure, increasing human resource capacity, applying innovative learning methods, and utilising technology as a medium for communication and collaboration. This study emphasises that digital transformation is not only an option but a strategic necessity to achieve quality, professional, and sustainable education in the midst of changing times